Perancangan Aplikasi Injeksi SQL dan Implementasi Terhadap Serangan Vulnerability Pada Website - Trinugi Wira Harjanti; Muhammad Fachri (Sekolah Tinggi Teknologi Informasi NIIT, 2020)
Currently, the website has become a major driver of the various technologies used by many websites among government, industry, education, health and others. So many systems that rely on the website so that if found defective which causes the vulnerability published on the website when the website is vulnerable to lead the attack and considered unsafe. This study aims to build a webiste Vulnerebility Scanning software with Sql Injection vulnerabilities on the website and use the Website Injection applications to determine informationcontent of the website database without being noticed by the website administrator. Identification Scanning Vulnerebility conducted stratified by recognizing the url address of the website to be identified. Url address of the website done in sequential scanning starts from the beginning to the end address of the website url website url address in the range that is not defined by the user. Results from experiments conducted can be concluded that the webiste that has vulnerebility Sql Injection will be read by the application of Scanning Vulnerebility, as well as to websites that have vulnerebility. Use Injection Application webiste to find out information from a database table contents from websites that have vulnerebility sql injection.